Incidence and risk factors associated with caesarean section among Bangladeshi women: a retrospective cross-sectional study - Nargis, Sohelee; Khatun, Rabea; Saha, Kakali; Saha, Shilpi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Caesarean section is a lifesaving procedure in the presence of maternal and fetal complications. In recent decades the rate of caesarean section is increasing rapidly due to several associated risk factors. The objective of this study was to assess the prevalence and associated risk factors of C-sections among women at Kumudini Women's medical college. Methods: This retrospective cross-sectional study was conducted at the department of obstetrics and gynaecology in Kumudini Women's Medical College, Tangail, Bangladesh. The study was conducted during the period of July 2019 to January 2020. The total sample size this study was 2105. Results: Majority 696 (33.1%) of participants were aged between 18-24 years and followed by 464(22%) aged 25-30, 569 (27%) aged 31-35 and the rest 376 (17.9%) were aged 36-40 years. A significant association was noticed in respect of previous history of CS, gestation age and fetal weight with the type of delivery (p value, 0.000, 0.033, 0.021). whereas in parity there was no significant relationship with caesarean section (p value, 0.421). A significant association was noticed in respect of pre-eclampsia, eclampsia induction failure, fetal distress, APH, twin, malpresentation, and the type of delivery (p value, 0.02, 0.003, 0.001, 0.001, 0.002, 0.04, 0.03 and 0.1). Whereas in PROM there was no significant relationship with caesarean section (p value=0.1). Conclusions: This study concludes that the incidence of caesarean sections is seemed to be very high in Bangladesh. Although it is a life-saving procedure, it is important to choose carefully when performing a C-section birth.